Dampak Orientasi Kewirausahaan dan Inovasi Produk terhadap Kinerja Pemasaran Oleh-Oleh Khas kota Malang - Hidayat, Candra Wahyu; Putra, Yoan Santosa; Kowiyanto, Kowiyanto; Kartikaningrum, Lina (Manajemen & Bisnis Jurnal, 2026)
This study aims to examine how entrepreneurial spirit and innovative capabilities influence the marketing performance of Malang's specialty souvenirs, influenced by entrepreneurial orientation and product innovation. The data source for this study is primary data derived from a sample of Malang specialty souvenir shop owners. Sampling was conducted by MSME owners, managers, and MSME owners and managers. The data used in this study were 100 respondents. The data were processed using multiple linear regression. The results of this study indicate that: (1) Entrepreneurial orientation has a significant positive effect on the marketing performance of Malang Strudel (2) Product innovation has a significant positive effect on the performance of Malang Strudel (3) Entrepreneurial orientation and product innovation simultaneously have a significant positive effect on the marketing performance of Malang Strudel (4).